The development of performance and crossover teaching of singing: an interview with the singer and actress Bianca Tadini (Per Musi, 2021)
The present interview with the actress and crossover singer, Bianca Tadini, reveals aspects about her personal methods of study, learning, and teaching, considering a variate repertoire. It is a situation that demands considerable differences in vocal production, without, however, reminiscences between one style and another. The questions in the interview prioritize the decisions over situations in which the work exigencies were the alternation between Opera and Musical Theatre. The interviewee, in her opinion, relates which was the elements that facilitated her learning process, and what else she applies as in her study and the maintainability of her vocal technique as in her pedagogical approach.